Updating the African human mitochondrial DNA tree: Relevance to forensic and population genetics. (March 2017) - Heinz, Tanja; Pala, Maria; Gómez-Carballa, Alberto; Richards, Martin B.; Salas, Antonio
Highlights: The mtDNA phylogeny is commonly used in many forensic and biomedical applications. >2200 mitogenomes of recent African ancestry, namely, belonging to L(×M, N) haplogroups, were analyzed with the aim of improving the known worldwide phylogeny. We built maximum-parsimony phylogenetic trees and more than 300 new minor sub-clades were identified. Time to the Most Recent Common Ancestor (TMRCA) was computed for each node of the phylogeny using maximum-likelihood procedures. We comment on the relevance of phylogeography of African trees in forensic genetics, but also in anthropological studies, such as those related to the transatlantic slave trade. Abstract: Analysis of human mitochondrial DNA (mtDNA) variation plays an important role in forensic genetic investigations, especially in degraded biological samples and hair shafts. There are many issues of the mtDNA phylogeny that are of special interest to the forensic community, such as haplogroup classification or the post hoc investigation of potential errors in mtDNA datasets. We have analyzed >2200 mitogenomes of African ancestry with the aim of improving the known worldwide phylogeny. More than 300 new minor subclades were identified, and the Time to the Most Recent Common Ancestor (TMRCA) was estimated for each node of the phylogeny. Phylogeographic details are provided which might also be relevant to forensic genetics. The present study has special interest for forensic investigations because current analysis and interpretation of mtDNA casework rest on a solid worldwide phylogeny, as is evident from the role that phylogeny plays in popular resources in the field (e.g. PhyloTree), software (e.g. Haplogrep 2), and databases (e.g. EMPOP). Apart from this forensic genetic interest, we also highlight the impact of this research in anthropological studies, such as those related to the reconstruction of the transatlantic slave trade.